Pengaruh Intellectual Capital Terhadap Kinerja Keuangan Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Ni Komang Indah Supriani; Anak Agung Gede Suarjaya (Journal Of Business, Finance, and Economics (JBFE), 2024)
This study was conducted with the aim of obtaining results or empirical evidence regarding the influence of intellectual capital on the financial performance of companies listed. The data used in this study are financial report data from banking companies listed on the Indonesian Stock Exchange consecutively during the period 2020-2022. With a population of 32 companies, the sample determination was carried out using probability sampling and the research sampling technique used simple random sampling. The sample obtained for this study was 30 banking companies. The research data was processed using the SPSS 26.0 application with the analysis technique used, namely multiple linear regression analysis and classical assumption tests. The test results obtained from the study were that all components of intellectual capital, namely human capital efficiency (HCE), structural capital efficiency (SCE), and capital employed efficiency (CEE) had a positive and significant effect on the financial performance of banking companies as proxied by ROA. The results of this study are expected to provide benefits for company management to analyze the company's actions or strategies related to the management of intellectual capital because this affects the increase or decrease in profits and the company's financial performance.